The Effect of Concept Map Learning, Problem Solving and Achievement Motivation on Indonesian Learning Outcomes - Sunarni; Hari Karyono; Wawan Gunawan (Jurnal Mantik, 2022)
The purpose of this study was to determine the effect of concept map learning, problem solving and achievement motivation on Indonesian language learning outcomes. The method used in this research is experimental. The research population was all students of Class IX SMPN I and SMPN 2 Sidoarjo. As a sample, the students of Class IX A and B are 123 students. The results showed that: (1) there was a significant difference in Indonesian language learning outcomes between those taught using the concept map learning model and those taught problem solving by Class IX students at SMPN 1 and SMPN 2 Sidoarjo, (2) there was a significant difference in the results. learning Indonesian between students who have high achievement motivation and students who have low achievement motivation for Class IX students of SMPN 1 and SMPN 2 Sidoarjo, and (3) there is an interaction between concept map learning methods, problem solving and achievement motivation on the acquisition Indonesian language learning outcomes for Class IX students at SMPN 1 and SMPN 2 Sidoarjo. Based on the research results, the following suggestions can be made: (1) the application of the concept map method can be used as an alternative to improve student learning outcomes in the learning process, and (2) teachers should be able to be more creative in creating a pleasant atmosphere in the classroom.